Preface - Farnell, Rick (Rangifer, 2000)
The workshop organizers wanted to insure a wide range of content and meaningful participation of First Nation's people. The displays in the lobby and the caribou skin hut constructed on site greeted participants as they entered the Yukon Art's Center, the site of the conference. Elders told stories at the beginning of each session and these stories set a respectful tone to the whole conference. One of these stories is presented in these proceedings. In addition each session was accompanied by a selection of cartoons by Doug Urquhart to bring humor to participants during breaks. A selection of these cartoons is included in these proceedings so that the lighter side of our work can be referenced in the permanent record.